Systematics and ecology of Antarctic flavobacteria. In Proceedings of the 2nd international symposium on flavobacteria, cytophaga and related bacteria - Dobson, SJ; James, SR; Franzmann, PD; Burton, HR; Thomas McMeekin (1993)
No description available